2020
DOI: 10.21307/sjcapp-2020-005
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of group-based compassion-focused therapy for adolescents and their parents

Abstract: Background: The long-term negative consequences of mental health problems during adolescence highlight the need for effective treatments. Compassion-focused therapy (CFT) aims to help individuals to enhance their ability to support and care for themselves and to alleviate shame and self-stigmatization. Objective: This non-randomized controlled trial examined the effectiveness of group-based CFT on perceived stress and the extent of self-compassion in a clinical sample of adolescents receiving psychiatric care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…These results are in line with an emerging body of research relating to the benefits of CFT/CMT in supporting young people with mental health and well‐being difficulties (e.g. Bratt, Rusner, et al., 2020). Similarly, the findings support and build on other studies that demonstrate the effectiveness of CMT for reducing test anxiety (McEwan et al., 2018), lessening general anxiety (McEwan & Gilbert, 2016) and promoting self‐compassion in non‐clinical adult populations (Irons & Heriot‐Maitland, 2021; Maratos, Montague, et al., 2019).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These results are in line with an emerging body of research relating to the benefits of CFT/CMT in supporting young people with mental health and well‐being difficulties (e.g. Bratt, Rusner, et al., 2020). Similarly, the findings support and build on other studies that demonstrate the effectiveness of CMT for reducing test anxiety (McEwan et al., 2018), lessening general anxiety (McEwan & Gilbert, 2016) and promoting self‐compassion in non‐clinical adult populations (Irons & Heriot‐Maitland, 2021; Maratos, Montague, et al., 2019).…”
Section: Discussionsupporting
confidence: 86%
“…Early evidence appears to suggest that this approach can also be effective in supporting young people with mental health and well‐being difficulties (e.g. Bratt et al., 2020). For example, CFT was found to reduce psychopathic traits and challenging behaviours among incarcerated youth (Ribeiro da Silva et al., 2019).…”
Section: Compassion‐based Interventionsmentioning
confidence: 99%
“…It also remains to be tested whether this approach can be applicable to care-experienced boys and in a non-UK context. Low recruitment of boys has also been shown in a recent application of group CFT in Sweden (Bratt, Rusner and Svensson, 2020), an issue that needs further unpacking.…”
Section: Discussionmentioning
confidence: 88%
“…In turn, the qualities listed above might assist them in avoiding parental burnout and protecting their mental health. In addition, previous studies have shown that participation in interventions designed with compassion‐focused therapy (Bratt et al, 2020), mindfulness‐based compassion therapy (Jefferson et al, 2020), mindfulness‐based stress reduction (Jefferson et al, 2020) helped increase parental self‐compassion. These results can be carefully referenced in the future by both researchers and practitioners to help parents develop and strengthen their self‐compassion.…”
Section: Discussionmentioning
confidence: 99%